2014
DOI: 10.1039/c4cp02993c
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-stabilized Pt nanoparticles (NPs) as novel materials for catalytic gas sensing: influence of the ligand on important catalytic properties

Abstract: Different mono- and bifunctional amine ligands have been used to stabilize Pt NPs for catalytic H2 gas sensing. Depending on the chemical structure and properties of the ligand, the catalysts show different overall sensor performances, activation periods, and long-term stabilities. These sensor characteristics are put into relation with chemical processes like cleaning of the surface, degradation processes of the ligands and nanoparticle (NP) sintering. It has been found that during activation free adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“…In their seminal work published in 2000, [14] Wang and co‐workers showed that precious metal nanoparticles could easily be obtained without surfactant in alkaline ethylene glycol by reduction of H 2 PtCl 6 upon heat treatment and early on it was suggested and shown that such surfactant‐free synthesis is ideal to develop readily active catalysts [15,16,26] . Surfactant‐free metal NPs like Pt, [14] Ru, [14] Rh, [14] Co, [27] Os, [15] and alloys like PtRu, [4] PtFe, [28] PtSn, [29] PtRh [15] were obtained and demonstrated in applications ranging from chemical synthesis, [15,27,30,31] to electrochemical reactions like the oxygen reduction reaction [13] or electro‐oxidation of methanol [4,28] and ethanol [29] . One of the major advantages of surfactant‐free NP is that there is no need to activate them before catalysis and the synthesis is performed are relatedly low temperature, typically 150–160 °C for a thermally induced synthesis.…”
Section: Surfactant‐free Colloidal Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In their seminal work published in 2000, [14] Wang and co‐workers showed that precious metal nanoparticles could easily be obtained without surfactant in alkaline ethylene glycol by reduction of H 2 PtCl 6 upon heat treatment and early on it was suggested and shown that such surfactant‐free synthesis is ideal to develop readily active catalysts [15,16,26] . Surfactant‐free metal NPs like Pt, [14] Ru, [14] Rh, [14] Co, [27] Os, [15] and alloys like PtRu, [4] PtFe, [28] PtSn, [29] PtRh [15] were obtained and demonstrated in applications ranging from chemical synthesis, [15,27,30,31] to electrochemical reactions like the oxygen reduction reaction [13] or electro‐oxidation of methanol [4,28] and ethanol [29] . One of the major advantages of surfactant‐free NP is that there is no need to activate them before catalysis and the synthesis is performed are relatedly low temperature, typically 150–160 °C for a thermally induced synthesis.…”
Section: Surfactant‐free Colloidal Synthesesmentioning
confidence: 99%
“…The polyol synthesis is therefore a suitable approach for the toolbox, in particular due to its compatibility for electrochemical applications where free surfaces (further detailed in the Characterization section) are essential to allow an optimized electron transfer to/from the catalysts from/to the reactants. Furthermore, if the effect of surfactants or ligands should be studied, the NPs prepared by the surfactant‐free approach can thereafter be functionalized with different ligands [31,32] . This is simply achieved by performing phase transfer experiments.…”
Section: Surfactant‐free Colloidal Synthesesmentioning
confidence: 99%
“…Unprotected NPsa re stabilized by CO and OH À groups,w hich do not requireh arsh treatments for removal. [31] The thus-obtained NPs are ac onvenient building block to investigatea nd optimize NPs such as Pt for electrocatalysis, [32] sensing, [33] or chemical transformations. [34] Alkalinee thylene glycol (EG) has long been considered the most suitable solvent for the widelyu sed polyol process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, well dispersion of metal NPs were shown from elemental mapping images, as given in Figure . Unlike uncapped NPs on unfunctionalized supports, we believe that Pd/Pt NPs@PP‐3 might be stable and useful on account of the stabilization imparted by amine / alkoxy functionality of hypercrosslinked PP‐3 …”
Section: Resultsmentioning
confidence: 99%
“…Unlike uncapped NPs on unfunctionalized supports, we believe that Pd/Pt NPs@PP-3 might be stable and useful on account of the stabilization imparted by amine / alkoxy functionality of hypercrosslinked PP-3. [21] Powder X-ray diffraction (PXRD) of Pd@PP-3 and Pt@PP-3 shows the presence of broad peak at~2q = 208, corresponds to amorphous carbon peak ( Figure 3a). In addition, the presence of metal nanoparticles were confirmed from the appearance of several broad and weak intensity peaks.…”
Section: Resultsmentioning
confidence: 99%